Challenges of Slaughter Slab Management in Hong Local Government Area of Adamawa State. - Bode A. S; Adamu M. Y; Mary M (African Journal of Medicine, Surgery and Public Health Research, 2026)
Slaughter slabs are essential facilities for processing animals intended for human consumption; however, poor management can compromise meat safety, environmental sanitation, and public health. This study investigated the challenges of slaughter slab management in Hong Local Government Area of Adamawa State, Nigeria. A survey research design was adopted, using random sampling to select 100 respondents. Primary data were collected through structured questionnaires and focus group discussions, while secondary data were obtained from journals, proceedings, textbooks, brochures, and manuals. The data were analyzed using descriptive statistics, including tables, means, frequencies, and percentages. The findings indicate that poor administrative structure undermines the quality and safety of meat produced in the slaughter slab. In particular, the absence of adequate meat inspection raises serious concerns regarding meat safety and consumer health. The study further revealed that poor sanitary conditions within the slaughter slab environment negatively affect workers, users, nearby residents, and host communities, increasing their exposure to waterborne disease risks. The study concludes that effective slaughter slab management requires improved administrative oversight, sanitary infrastructure, and routine health supervision. It recommends that the local government provide adequate waste disposal facilities, appoint health personnel to supervise meat-processing practices, and educate butchers on hygienic meat handling, processing, and packaging. These findings contribute to public health and environmental management discourse by highlighting the need for stronger institutional support and hygiene-based governance in local slaughter slab operations.